PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATA KULIAH PENGANTAR MANAJEMEN MELALUI METODE PROJECT BASED LEARNING - Ambarwati, Titiek (Univesitas Muhammadiyah Malang, 2019)
This research is a classroom action research in the introductory management course taken by the first semester students (first semester). This study was conducted to improve student motivation and learning outcomes in learning management introductory subjects. The method used through the assignment approach (project based learning, data collection techniques with tests and non-tests. Data analysis by comparing learning outcomes before and after applying project based learning learning methods. The results of the study showed an increase in student motivation and learning outcomes. During the learning process there are obstacles, namely face-to-face time constraints.